2000
DOI: 10.1073/pnas.97.8.3862
|View full text |Cite
|
Sign up to set email alerts
|

Targeted inhibition of transcription elongation in cells mediated by triplex-forming oligonucleotides

Abstract: Triple-helix-forming oligonucleotides (TFOs) bind in the major groove of double-stranded DNA at oligopyrimidine⅐oligopurine sequences and therefore are candidate molecules for artificial gene regulation, in vitro and in vivo. We recently have described oligonucleotide analogues containing N3-P5 phosphoramidate (np) linkages that exhibited efficient inhibition of transcription elongation in vitro. In the present work we provide conclusive evidence that np-modified TFOs targeted to the HIV-1 polypurine tract (PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
98
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(104 citation statements)
references
References 30 publications
2
98
1
Order By: Relevance
“…6+73 28 a Reading of kinetic fluorometric GUS assay of 1 mg protein extract+ b Relative signal intensity of the full-length hybridization bands in Figure 6 calculated using the ImageQuant computer program+ c The figures in brackets are standard errors+ RNA occurred, substantial amounts of full-length GUS: Sat RNA persisted, suggesting that, if RNAi-mediated degradation was operational, it was relatively inefficient+ Alternatively, the truncated GUS:Sat RNA could have been produced by transcription that was prematurely terminated by the formation of RNA/DNA triplexes+ Triplex-forming oligonucleotides have been shown to inhibit transcription elongation in animal cells (Faria et al+, 2000)+ The satellite-derived ;22 nt RNAs in the PLRVinfected p35GUS:sat plants may similarly form triplexes with the homologous DNA sequences in the transgene and inhibit transcription elongation+ The coexistence of both full-length GUS:Sat RNA and truncated RNA, that we observed, might have been due to different levels of the satRNA and the resultant transcription-terminating ;22-nt RNAs in different cell types; the levels of these RNAs could be relatively high in the phloem and phloemassociated cells where the virus replicates, leading to significant levels of transcription termination and truncated RNA, whereas the RNAs that spread into the uninfected cells could be at insufficient concentrations to cause premature termination+ Pooling the transcripts from all the cell types, as we did by extracting from whole-tissue samples, would then be expected to give a population of both truncated and full-length transcripts+…”
Section: Accumulation Of Truncated Rna In P35gus:sat Plants Was Assocmentioning
confidence: 99%
“…6+73 28 a Reading of kinetic fluorometric GUS assay of 1 mg protein extract+ b Relative signal intensity of the full-length hybridization bands in Figure 6 calculated using the ImageQuant computer program+ c The figures in brackets are standard errors+ RNA occurred, substantial amounts of full-length GUS: Sat RNA persisted, suggesting that, if RNAi-mediated degradation was operational, it was relatively inefficient+ Alternatively, the truncated GUS:Sat RNA could have been produced by transcription that was prematurely terminated by the formation of RNA/DNA triplexes+ Triplex-forming oligonucleotides have been shown to inhibit transcription elongation in animal cells (Faria et al+, 2000)+ The satellite-derived ;22 nt RNAs in the PLRVinfected p35GUS:sat plants may similarly form triplexes with the homologous DNA sequences in the transgene and inhibit transcription elongation+ The coexistence of both full-length GUS:Sat RNA and truncated RNA, that we observed, might have been due to different levels of the satRNA and the resultant transcription-terminating ;22-nt RNAs in different cell types; the levels of these RNAs could be relatively high in the phloem and phloemassociated cells where the virus replicates, leading to significant levels of transcription termination and truncated RNA, whereas the RNAs that spread into the uninfected cells could be at insufficient concentrations to cause premature termination+ Pooling the transcripts from all the cell types, as we did by extracting from whole-tissue samples, would then be expected to give a population of both truncated and full-length transcripts+…”
Section: Accumulation Of Truncated Rna In P35gus:sat Plants Was Assocmentioning
confidence: 99%
“…[5][6][7][8] In addition, these compounds have been used to inhibit transcription and to stimulate site-directed recombination of a co-transfected donor DNA, resulting in correction of a mutation in the target gene. [9][10][11][12] TFOs have also been used to study mechanisms of DNA damage and repair, recombination and structurally induced genomic instability. Previous studies have demonstrated that triplex formation itself induces mutagenesis and stimulates DNA repair.…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence support the concept that simple triplexes exist in vivo including the following: oligonucleotidetargeted mutagenesis at R⅐Y tracts in mammalian cells (15)(16)(17)(18); triplex-mediated inhibition of replication and transcription (19,20); transcription-dependent recombination induced by intramolecular triplex formation in E. coli (21); chemical modification studies in situ (22,23); psoralen photobinding in living cells (24,25); and deletion analyses on poly(R⅐Y) sequences as a function of transcription and negative supercoil densities in vivo (26). Because triplexes are known to exist and to inhibit transcription in vitro and in vivo (reviewed in Ref.…”
mentioning
confidence: 95%